MENINGKATKAN KEMAMPUAN GURU DALAM MERANCANG RPP KURIKULUM 2013 MELALUI TUTOR SEBAYA DI SD NEGERI 008 RAMBAH - Erwita Erwita (STKIP ROKANIA, 2018)
This study aims to see how far the activities of peer tutors head teachers can improve teacher competence in the preparation of Learning Implementation Plan (RPP). As for the results obtained from this study, peer tutor activities proved to be scientifically able to improve the competence of teachers in preparing the RPP in SDN 008. This is evidenced by the increase in the number of good quality RPP also increased from 67% to 78% after peer tutor.